Using the Ishikwa diagram for problem analysis in the laser cutting process - Alexandru-Vasile Oancea; Corneliu Rontescu; Ana-Maria Bogatu; Dumitru-Titi Cicic (Journal of Research and Innovation for Sustainable Society)
Laser cutting is a computer numerically controlled process widely used in the automotive industry for cutting metal materials needed to manufacture parts used in automobile production. The production process represents all the conscious actions of a company's employees carried out with the help of various machines, equipment, or installations on raw materials, materials, or other components to transform them into products or services with a certain market value. The Ishikawa diagram, also known as the cause-and-effect diagram, is often used in industrial process analysis, defect prevention, and product design processes. The paper presents the results of the research conducted on the use of the Ishikawa diagram in analyzing the causes that lead to negative effects in the laser cutting process of S235JRH structural steel pipes. After defining the problem, by applying the "WHO, WHAT, WHERE, WHEN, HOW MUCH, HOW, WHY" method, all possible causes were identified using the "5 Whys" method. The analysis identified 11 probable causes, and through further analysis, it was concluded that 3 of them were already present in the process, influencing the laser cutting of the pipes and generating quality problems. All the identified causes built the Ishikawa diagram consisting of 7Ms.